Analysis on key influence factors of air source heat pumps with field monitored data in Beijing. (December 2021) - Xu, Zhaowei; Zhao, Wenyuan; Shao, Shuangquan; Wang, Zhichao; Xu, Wei; Li, Hao; Wang, Yichao; Wang, Wei; Yang, Qiang; Xu, Ce
Highlights: The SCOP is 1.54 ∼ 2.95 through field monitored data of 103 projects. Key factors of ASHPs include terminal type, load rate and control strategy. The mean SCOP is 2.37 for floor heating and 2.10 for radiator. The SCOP improves 11.5% with 10% increase in load rate for fixed frequency systems. Abstract: Air source heat pumps (ASHPs) are in wide use around the world, and their practical applications and continual improvement have attracted great attention. To more fully understand their actual-operational performance, field monitoring was carried out on 103 ASHP systems in Beijing during the 2018–2019 heating season, accompanied by a decoupling analysis of the key influencing factors on performance. The observed seasonal coefficient of system performance ( SCOP ) ranged from 1.54 to 2.95, with an average of 2.21. Based on this large sample, three key influencing factors were identified, namely: terminal type, operating load rate and capacity regulation characteristics. In terms of terminal type, floor heating systems obtained a relatively high SCOP of 2.37 on average, due to the lower water temperature, compared with a radiator system average of 2.10. As for load rate, oversized capacity is a common problem: the recorded average annual operating load rate was only around 0.48, which resulted in high energy consumption from frequent on–off losses, and also increased power consumption by the circulating pump. This analysis provides engineering reference and support for the design and technological improvement of ASHP systems.